1979
DOI: 10.1073/pnas.76.1.469
|View full text |Cite
|
Sign up to set email alerts
|

Photomutagenesis by chlorinated phenothiazine tranquilizers.

Abstract: Phenothiazine tranquilizers are widely used pharmaceuticals that have been associated with side effects, such as formation of cataracts, that seem related to light exposure. Because patients may use them over extensive time periods, it is important to determine what deleterious cellular effects these drugs may cause and, if possible, to select or design drugs that do not cause such effects. The results reported here demonstrate that chlorinated phenothiazine drugs can be photoactivated to mutagenic species, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The lack of genotoxicity of CPZ alone is consistent with a previous study that showed CPZ to be strongly positive for mitotic recombination in strain D7 under conditions of photomutagenicity, but not under conventional assay conditions in the dark [Gocke, 1996]. Despite its capacity to intercalate, CPZ without photoactivation gave negative results in bacterial assays for frameshift mutations [Jose, 1979;Mortelmans et al, 1986;Gocke, 1996].…”
Section: Discussionsupporting
confidence: 91%
“…The lack of genotoxicity of CPZ alone is consistent with a previous study that showed CPZ to be strongly positive for mitotic recombination in strain D7 under conditions of photomutagenicity, but not under conventional assay conditions in the dark [Gocke, 1996]. Despite its capacity to intercalate, CPZ without photoactivation gave negative results in bacterial assays for frameshift mutations [Jose, 1979;Mortelmans et al, 1986;Gocke, 1996].…”
Section: Discussionsupporting
confidence: 91%
“…Nishio, Y., T. Kakizoe, M. Ohtani, S. Sato, T. Sugimura and S. (1)(2)(3)(4)(5)(6)(7). Although many phototoxic compounds are photomutagenic, others, such as retinoids and nitro-benzodiazepines are not photomutagenic (8,9).…”
mentioning
confidence: 99%
“…The results of this study suggest for the first time that drugs with weak photosensitivity when administered long-term also are carcinogenic. The enhanced tumour development in the case of CPZ seems likely to have stemmed from that drug's phototoxicity since the drug has no known immunosuppressive or mutagenic properties although in vitro it is photomutagenic when activated by UVR (Jose, 1979). In this study, combined CPZ-UVR therapy compared to UVR alone reduced the latent period of appearance of premalignant skin lesions (papillomas and keratoacanthomas) and increased the rate of conversion of premalignant to malignant lesions.…”
Section: Discl'ssionmentioning
confidence: 67%